Exploring the theoretical foundations of visual art programmes for people living with dementia. (August 2018) - Windle, Gill; Gregory, Samantha; Howson-Griffiths, Teri; Newman, Andrew; O'Brien, Dave; Goulding, Anna
Despite the growing international innovations for visual arts interventions in dementia care, limited attention has been paid to their theoretical basis. In response, this paper explores how and why visual art interventions in dementia care influence changes in outcomes. The theory building process consists of a realist review of primary research on visual art programmes. This aims to uncover what works, for whom, how, why and in what circumstances. We undertook a qualitative exploration of stakeholder perspectives of art programmes, and then synthesised these two pieces of work alongside broader theory to produce a conceptual framework for intervention development, further research and practice. This suggests effective programmes are realised through essential attributes of two key conditions (provocative and stimulating aesthetic experience; dynamic and responsive artistic practice). These conditions are important for cognitive, social and individual responses, leading to benefits for people with early to more advanced dementia. This work represents a starting point at identifying theories of change for arts interventions, and for further research to critically examine, refine and strengthen the evidence base for the arts in dementia care. Understanding the theoretical basis of interventions is important for service development, evaluation and implementation.